(untitled) (Faculty of Education Scientific Journal, 2025)
This study aimed to investigate the Self- assessment of the level of Class teaching observation skills among students’ teachers at the College of Education at Sirte University. . To achieve the objective of the study, the descriptive design was utilized in this study, where questionnaire used, which consisted of (20) items distributed on three domains: Lesson Planning Skills, Implementation and Evaluation Skills, and Personal Situational Skills. After the confirmation of the validity and reliability, the questionnaire applied on the main sample was chosen in a comprehensive inventory method, which consisted of (61) students’ teachers, including (30) from the humanities, and the others (31) from the applied sciences. Results revealed that the level of assessment of student’s teachers for the degree of their acquisition of classroom teaching observation skills came high in all three domains, and the arithmetic means were respectively (3.8131- 3.8051- 3.7951). The results also revealed that there were no statistically significant differences between the average estimates of students teachers in the domain of " Lesson Planning Skills " due to the specialization’ variable, while there were statistically significant differences between their estimates in another two domains, in favor of students teachers in the applying sciences.